PENGARUH BUDAYA HUKUM DI LOMBOK TENGAH DALAM PENEGAKAN HUKUM TINDAK PIDANA KESUSILAAN - WULANDARI, LAELY; AMIN, IDI (GANEC SWARA, 2024)
Lawrence M. Friedman stated that the effectiveness of law enforcement depends on three elements of the legal system, namely legal structure, legal substance, and legal culture. Criminal Acts Against Morality are one of the fairly complex acts in terms of law enforcement. Lombok Tengah was once in the spotlight regarding several criminal acts against morality that were not fully investigated. Empirical legal research methods were used to find answers to the questions of what factors influence law enforcement and the role of legal culture in enforcing criminal acts against morality. Legal regulation factors and legal understanding of law enforcement officers are part of the inhibiting factors, while adequate facilities and infrastructure are supporting factors in enforcing the law on Criminal Acts Against Morality in Lombok Tengah. The patriarchal legal culture of society, victims who are embarrassed to the point of withdrawing their reports, and slow performance factors from officers make law enforcement on criminal acts against morality not run as it should. Socialization of regulations on crimes against morality, increasing the capacity of law enforcement officers and strengthening victims, victims' families and the community are part of the solution in enforcing the law on crimes against morality in Lombok Tengah